2019
DOI: 10.1111/mpp.12900
|View full text |Cite
|
Sign up to set email alerts
|

Single gene enables plant pathogenic Pectobacterium to overcome host‐specific chemical defence

Abstract: Plants of the Brassicales order, including Arabidopsis and many common vegetables, produce toxic isothiocyanates to defend themselves against pathogens. Despite this defence, plant pathogenic microorganisms like Pectobacterium cause large yield losses in fields and during storage of crops. The bacterial gene saxA was previously found to encode isothiocyanate hydrolase that degrades isothiocyanates in vitro. Here we demonstrate in planta that saxA is a virulence factor that can overcome the chemical defence sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…A large number of studies have shown that the combined use of pathogenic fungi and other biological control methods (including bacteria, plant-derived insecticides, attractants, and natural enemies) can significantly improve the effectiveness of insect-pathogenic fungi (Figure 4) (Zhao et al, 2014;Van den Bosch et al, 2019). Fungus-based insecticides have great potential as a form of pest control.…”
Section: Application Of Pathogenic Fungi For Biological Control Biological Control Of Insect Pestsmentioning
confidence: 99%
“…A large number of studies have shown that the combined use of pathogenic fungi and other biological control methods (including bacteria, plant-derived insecticides, attractants, and natural enemies) can significantly improve the effectiveness of insect-pathogenic fungi (Figure 4) (Zhao et al, 2014;Van den Bosch et al, 2019). Fungus-based insecticides have great potential as a form of pest control.…”
Section: Application Of Pathogenic Fungi For Biological Control Biological Control Of Insect Pestsmentioning
confidence: 99%
“…One replicate was excluded from the analysis because the H. axyridis larva had moulted to the fourth larval instar. Survival data were analysed using a parametric survival regression model with a log-logistic hazard distribution in R (Therneau, 2015). Logrank tests with Benjamini and Hochberg correction were performed using the r package survminer (Kassambara & Kosinski, 2018).…”
Section: Survival Rate Of Flea Beetle Larvae With Low and High Gls mentioning
confidence: 99%
“…GBCs can be confronted with these compounds, depending on the gut structure of the insect and their spatial distribution in the gut (foregut, midgut, or hindgut). Several studies showed that members of GBCs possess detoxification mechanisms, which may be beneficial to the GBCs as well as their hosts [15,38].…”
Section: Gbcs Are Supporting Diptera To Exploit Specific Niches and Fmentioning
confidence: 99%
“…Several of these bacteria possess a saxA gene encoding for a hydrolase that can break down various plant-produced isothiocyanates [49]. Deletion of the saxA gene in one of the gut microbes, Pectobacterium carotivorum, prevented this bacterium from being able to degrade plant material [38]. Whether these gut microbes are essential for the larvae to detoxify their host plant's defense system and/or their possession of the detoxification enzymes to occupy this specific niche is not clear yet.…”
Section: Gbcs Are Supporting Diptera To Exploit Specific Niches and Fmentioning
confidence: 99%